Efficacy of Benzocaine, Eugenol, and Menthol as Anesthetics for Freshwater Angelfish - Romaneli, Rafael de Souza [UNESP]; Boaratti, Andre Zuffo [UNESP]; Rodrigues, Andressa Tellechea [UNESP]; Almeida Queiroz, Daniel Monge de [UNESP]; Khan, Kifayat Ullah [UNESP]; Torres Nascimento, Thiago Matias [UNESP]; Kochenborger Fernandes, Joao Batista [UNESP]; Menegasso Mansano, Cleber Fernando (Wiley-Blackwell, 2018)
For the production and commercialization of ornamental fish species, it is indispensable to collect biometric data that facilitate the selection of animals for trade and genetic improvement of the stock. However, during the handling process, fish receive more stress if proper anesthetics are not used. Thus, application of appropriate anesthetics is an important tool for minimizing stress in animals. The objective of this study was to determine the effective concentrations of benzocaine, eugenol, and menthol for achieving anesthesia in Freshwater Angelfish Pterophyllum scalare and to develop induction and recovery response curves for different concentrations of these anesthetics. In total, 75 fish were exposed to five concentrations of the three anesthetics in a completely randomized design: benzocaine at 60, 85, 110, 135, and 160mg/L; eugenol at 40, 80, 120, 160, and 200mg/L; and menthol at 50, 75, 150, 200, and 250mg/L. Each concentration (5fish/concentration) consisted of five replicates, with each replicate represented by a single fish. The results indicated that the tested substances met the criteria of anesthetic efficiency. The effective concentrations of benzocaine, eugenol, and menthol for the anesthesia of Freshwater Angelfish were identified as 89.25, 90.6, and 92.1mg/L, respectively.